Phenolic compounds and biological potential of Eugenia uniflora L.: A short review - Magalhães, Cássia Gonçalves; Sola, Isabela Maria Macedo Simon; Alberti, Aline; Ascari, Jociani; Nunes, Domingos Sávio (Eclética Química, 2025)
Eugenia uniflora L. (Myrtaceae) is native to Brazil and it is known as pitanga. In traditional medicine, this species is used to treat cough, skin allergies and asthma. Different parts of this plant displayed insecticidal, antimicrobial, and antioxidant activities. The main phenolic compounds found in the extracts of this species are flavonoids and tannins, which display relevant biological activities. This review shows recent phytochemical studies on E. uniflora, emphasizing the phenolic compounds, including a description of methods of extraction of these metabolites. Besides, the diversified biological activities and the potential of this plant for the food industry are reported. The pharmacological and nutraceutical potential attributed to E. uniflora justify the growing scientific interest in this species.